What Zombie Feminist Bouffons Can Offer Applied Theatre: Seduction and Provocation in Death Married My Daughter - Kandil, Yasmine; MacArthur, Michelle (Theatre Research in Canada / Recherches théâtrales au Canada, 2018)
Starting from applied theatre scholar Adrian Jackson’s assertion that a combination of seduction and provocation is crucial to the success of authentic intervention in theatre for social change, this article looks outside of traditional Forum Theatre for a model of this practice. Using Danya Buonastella and Nina Gilmour’s bouffon clown show Death Married My Daughter as its case study, this article draws on scholarship in the areas of applied theatre and feminist theory to examine what audience engagement and intervention might look like in the unsettling times in which we live. The performers’ use of bouffon seduces and provokes their audience in order to elicit empathy for the characters, expose the presence of neoliberal and postfeminist ideologies in women’s lives, and implicate their audience in a project of socio-political change. The article concludes by suggesting what applied theatre practitioners could learn from theatre that does not require direct intervention in the action on stage but nevertheless pushes the audience out of a comfortable, passive spectatorship.